The experience of pregnant women in accessing maternal care during pregnancy: a qualitative study - Fatimah, Siti; Wulandatika, Darmayanti; Mahfuzhah Deswita Puteri; Yustan Azidin (Universitas 'Aisyiyah Yogyakarta, 2024)
Antenatal care is important in health optimization and early detection of maternal and fetal problems during pregnancy. In developing countries, access to prenatal care is still not optimal, which is indicated by the high maternal mortality rate in Indonesia of 173 per 100,000 live births. Midwives have an important role in pregnancy services by providing midwifery care that focuses on the needs of women. This study aims to determine the experience of pregnant women in South Kalimantan in accessing midwifery services during pregnancy. This study is qualitative and uses a generic exploratory approach. The research Data were taken using in-depth interviews with five pregnant women and analysed using the Collaizi framework with attention to the rigour of research data. The results of this study indicate that socio-cultural and socio-economic factors significantly impact the choice of healthcare facilities used. The existence of health policies and programs that focus on the needs of women is expected to optimize the quality of midwifery services.